Fostering Students' Autonomy and Engagement in EFL Classroom Through Proximal Classroom Factors: Autonomy-Supportive Behaviors and Student-Teacher Relationships - Han, Kunni (Frontiers in Psychology, 2021)
Language learning achievement depends on student engagement which is at the center of attention these days. To assist students to become autonomous and independent learners, providing a social and supportive context is beneficial through autonomy-supportive and interaction. When learners are given the freedom to make choices about their education, they are likely to feel more enthusiastic and engaged. Moreover, learners’ academic and social practices are largely influenced by educators, who play a major role as social agents and the function of the educators as the most dominant figures is the cornerstone of the language classroom. As there is a dearth of studies that have considered teachers and student interactions among all other effective issues and their significant effect on students’ autonomy and engagement from the perspective of self-determination theory (autonomy support), the present review endeavors to focus on teacher-student interaction from the social perspective and their effects on student engagement in EFL classrooms. Subsequently, some implications are presented to elucidate the practice of teachers, students, teacher educators, materials developers.